Wood Quality of Xylia Xylocarpa and Khaya Ivorensis Planted in Sabah - Josue, James (2002)
Xylia xylocarpa and Khaya ivorensis are two fast-growing trees that are currently planted on trial basis in Sabah. The wood quality of trees grown in Sabah may differ from those grown in other places due to the environmental factors. Five 9-year-old trees of each species were extracted from their respective plots at Luasong, Tawau. Wood specimens were prepared from three height levels; bottom, middle and top, at the inner and outer radial positions. The within-tree and between-tree variations of anatomical, physical and mechanical properties of these species were analysed. The characteristics of X xylocarpa are comparable to a number of local popular hardwood species, indicating its suitability for heavy construction uses.